PENGARUH TAX PLANNING DAN FAKTOR LAINNYA TERHADAP NILAI PERUSAHAAN - Effivani; Muhammad Arief Effendi (E-Jurnal Akuntansi TSM, 2023)
This study aims to determine the effect of tax planning, institutional ownership, profitability, liquidity, dividend policy, debt policy, managerial ownership, and firm size on firm value. The object used in this research is manufacturing companies listed on the Indonesia Stock Exchange (IDX) consistently from 2019 to 2021.The sampling method used in this study is purposive sampling, there are 43 manufacturing companies listed on the Indonesia Stock Exchange (IDX) which are the samples of this study. The results of the study show that profitability and debt policy have a positive effect on firm value. Meanwhile, tax planning, institutional ownership, liquidity, dividend policy, managerial ownership, and firm size have no effect on firm value.